El juego en la represión de los efectos psicosociales en la familia de los niños y niñas de 3 a 4 años de edad en la Unidad Educativa del milenio Ángel Polibio Chaves del cantón San Miguel provincia Bolívar en el periodo 2024 - Guzmán Cayambe, Jesenia Joselin (2024)
The family is considered a fundamental unit in society, and its definition may vary according to the cultural, social and emotional context. At a global level, the family is important for the emotional and social development of children, providing support and protection for all its members, transmitting values and traditions, providing stability and social cohesion. For children under 5 years old, the family plays a very important role, because at this age emotional, social, cognitive and physical skills are developed, so ideally a child should have the presence and time of their parents at all times in a healthy, safe, loving, patient environment that allows the child to grow and develop optimally. However, due to external factors, many parents are unable to provide this type of family union that every child requires. The psychosocial effects generated by family problems can significantly affect the development of children, even more in the ages of 3 to 4 years, as it can cause a number of difficulties. Therefore, this research work seeks to mitigate them, with the theme of the game in the repression of psychosocial effects in the family of children aged 3 to 4 years in the Millennium Educational Unit Angel Polibio Chaves of the canton San Miguel Bolívar province in the period 2024, in order to have an active participation in children in both social and emotional behavior.